Pengembangan Desa Wisata Melalui Sosialisasi Pembentukan Kelompok Sadar Pariwisata (POKDARWIS) - Abdurrahman Abdurrahman; Putri Ayu Hidayatur Rafiqah; Khairussalam Khairussalam; Said Khaidir; Bhentar Syamboga; Aulia Fajar Nurrahman; Dinar Adis Tiyani; Erna Rusyida Sa’adiyah; Novita Yuliana; Elisa Ivo Pratiwi (Wadah Inovasi Indonesia, 2021)
Paring Tali Village is one of the villages in Simpang Empat District, Banjar Regency, South Kalimantan Province. Paring Tali village has tourism potential that can be developed as a tourist village. Paring Tali (Parta) Lake is one of the tourism potentials with an area of ​​5 ha. The development of Lake Parta tourism has been carried out since 2015 but is not managed sustainably due to a land dispute between the village government and the private sector. Therefore, through the socialization of tourism village development, it is expected to empower village communities in tourism management. The purpose of Community Service is to broaden the horizons of village officials, empower communities related to the development of tourist villages, and increase public awareness of the importance of managing tourist villages. The method used is a descriptive analysis method with a qualitative approach. The implementation of the empowerment program is carried out through three stages, namely survey, socialization, and branding. This community service increases public awareness of the importance of tourism villages, and the Paring Tali Village is willing to form a tourism awareness group (POKDARWIS).